German short forms of the Oral Health Impact Profile - John MT, Miglioretti DL, LeResche L, Koepsell TD, Hujoel P, Micheelis W. (Blackwell Synergy, 2006)
We report the development and psychometric evaluation of short forms of the Oral Health Impact Profile German version (OHIP-G) - an instrument to assess oral health-related quality of life (OHRQoL).